The Impact of International Cooperation on the Development of Renewable Energy Sources in Kazakhstan - A. S. Smagulova; G. K. Kenzhegulova; Z. T. Satpayeva; A. M. Myrzakhmetova; A. T. Yerimpasheva (Экономика: стратегия и практика, 2024)
In recent decades, renewable energy sources (hereinafter - RES) have become an increasingly important component of global energy policy, especially in the context of the need for sustainable development and the fight against climate change. This study analyzes the role of international cooperation in the development of RES in Kazakhstan and assesses its impact on national strategies for reducing greenhouse gas emissions and transitioning to sustainable energy. The research employs cluster analysis to identify groups of partner countries with similar energy and environmental profiles, complemented by Ward’s dendrogram and scenario analysis to predict the future directions of international cooperation. Data from the Bureau of National Statistics of the Republic of Kazakhstan, including greenhouse gas emissions, the share of renewable energy in total energy consumption, water resource availability, fuel exports, and energy intensity, were utilized. Three main clusters were identified: countries with advanced technologies in the field of RES, countries with emerging RES markets, and countries focused on hydrocarbon exports but seeking to diversify their energy resources. Cluster analysis revealed that Kazakhstan falls into the group with high energy intensity and a low share of RES in the energy balance (1.8%). Scenario analysis demonstrated that with active international cooperation, the share of RES in Kazakhstan could increase to 10-12% by 2030, and energy intensity could decrease, leading to a reduction in CO2 emissions. For future research, an in-depth analysis of Kazakhstan’s international cooperation in the field of renewable energy sources with an emphasis on regional specifics is recommended.